2023
DOI: 10.21203/rs.3.rs-2362750/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spaceflight alters insulin and estrogen signaling pathways

Abstract: Organismal adaptations to spaceflight have been characterized at the molecular level in model organisms, including Drosophila and C. elegans. Here we extend molecular work to energy metabolism and sex hormone signaling in mice and humans. We found spaceflight-induced changes in insulin and estrogen signaling in rodents and humans. Murine changes were most prominent in the liver, where we observed inhibition of insulin and estrogen receptor signaling with concomitant hepatic insulin resistance and steatosis. Ba… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…While these systemic stresses appear universal, individuals experience varying degrees of dysregulation, necessitating astronaut-specific precision medicine to ensure safe space travel for all. Data from I4 and JAXA missions reveal both universal changes (increased inflammation and mitochondrial stress), independent of sex and ethnicity, and sex-specific variations (insulin and estrogen changes in females) 4,8,33 . By aggregating these findings, we can annotate systemic changes and construct a molecular fingerprint for key alterations indicated that individualized astronaut healthcare is crucial.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While these systemic stresses appear universal, individuals experience varying degrees of dysregulation, necessitating astronaut-specific precision medicine to ensure safe space travel for all. Data from I4 and JAXA missions reveal both universal changes (increased inflammation and mitochondrial stress), independent of sex and ethnicity, and sex-specific variations (insulin and estrogen changes in females) 4,8,33 . By aggregating these findings, we can annotate systemic changes and construct a molecular fingerprint for key alterations indicated that individualized astronaut healthcare is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial and immune function are interconnected, impacting insulin and estrogen signaling, and posing heightened health risks for the female reproductive system 50 . An integrated analysis of murine, JAXA cfRNA, and I4 scRNA-seq data revealed altered mRNA levels during and after spaceflight, affecting mitochondrial metabolic pathways, particularly lipid metabolism and oxidative stress 4 . These changes contribute to heightened health risks associated with reproductive hormone synthesis.…”
Section: Cellular Adaptations In Response To Spaceflightmentioning
confidence: 99%
See 1 more Smart Citation
“…This enzyme superfamily is believed to account for 75% of total drug metabolism 28 . Indeed, CYPs have recently been suggested to be altered in flight due to alterations in insulin and estrogen signaling 29 . Several CYP450 genes are highly polymorphic, producing enzyme variants that cause variability in drug-metabolizing effects between groups.…”
Section: Introductionmentioning
confidence: 99%
“…While still in its infancy [24][25][26], it seems clear that combining -omics data from space-flown model organisms, such as C. elegans, Drosophila, and rodents, with astronaut data can accelerate the discovery process, in part by compensating for the current rarity of human space -omics datasets [22,27]. For example, C. elegans, rodents, and humans all display alterations in insulin-linked gene expression in response to spaceflight [28]. Given the central role of insulin in human health and longevity on Earth [29], it is highly likely this system is equally important to maintain in space.…”
Section: Introductionmentioning
confidence: 99%